A Study of Frequency and Factors Associated with Depression Among Adult Diabetics in Urban Areas of Davangere, Karnataka - Taranum, Arshiya; Angadi, Navinkumar; Shakeel, Md (National Journal of Community Medicine, 2016)
Background: Diabetes is growing epidemic in India with more than 62 million diabetic individuals currently diagnosed with the disease. Diabetes mellitus (DM) is one of such chronic medical conditions that could be associated with depressive syndromes. , recognition of depression is important Objective: Objectives of the study were to determine the prevalence of depression among adult diabetic patients and to study the associated socio-demographic and clinical factors with depression among adult diabetic patients. Materials and Methods: This Community basedcross-sectional study was conducted among 90 diabetic patients in Urban Health training Centre located in the field practice area of JJM Medical College who gave informed written consent. Results: Among 90 study participants 52%) were males and 43 (48%) were females. The prevalence of depression among the study subjects was found to be 47%. However, severe depression was found in only 26% of diabetic patients. Conclusions: Depression, found amongnearly half of the subjects,was associated with factors like higher age, female gender, lower socioeconomic status, presence of complications/co-morbidities, longer duration of treatment and treatment with insulin.Although majority of diabetic patients were potential cases of depression, the great majority were under-recognized and undertreated.